2019
DOI: 10.1186/s13071-018-3254-1
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to common insecticides and detoxifying enzyme activities in Anopheles sundaicus (sensu lato) after cessation of indoor residual spraying of insecticides in the Jaffna Peninsula and its surroundings in northern Sri Lanka

Abstract: BackgroundSri Lanka has been malaria-free since 2013 but re-introduction of malaria transmission by infected overseas travelers is possible due to a prevalence of potent malaria vectors. Knowledge of the insecticide resistance status among Anopheles vectors is important if vector control has to be reintroduced in the island. The present study investigated the insecticide susceptibility levels and resistance mechanisms of Anopheles sundaicus (sensu lato) (previously classified as Anopheles subpictus species B) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The four anopheline species collected in Jaffna city were resistant to DDT despite the cessation of DDT use for indoor residual spraying (IRS) in Jaffna in early 1970s. Resistance to DDT declined slowly after cessation of use, but increased again after 1983 due to a glutathione-S transferase-based mechanism, postulated to be initially caused by DDT and subsequently by exposure to the malathion used for IRS and other organophosphates used for controlling agricultural pests [2,27,45,46]. The results confirm that An.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The four anopheline species collected in Jaffna city were resistant to DDT despite the cessation of DDT use for indoor residual spraying (IRS) in Jaffna in early 1970s. Resistance to DDT declined slowly after cessation of use, but increased again after 1983 due to a glutathione-S transferase-based mechanism, postulated to be initially caused by DDT and subsequently by exposure to the malathion used for IRS and other organophosphates used for controlling agricultural pests [2,27,45,46]. The results confirm that An.…”
Section: Discussionsupporting
confidence: 69%
“…stephensi in Jaffna was resistant to DDT and deltamethrin [15], we now show that there are no mutations in the sequenced IIS6 segment of the VGSC protein in this mosquito. Resistance may, therefore, be caused by other mechanisms such as increased activities of detoxifying enzymes [27,45,46] and this merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This study reports contrasting differences in insecticide resistance among two molecular forms of the Subpictus Complex and the occurrence of kdr mutations that confer resistance against DDT and pyrethroids. These two molecular forms are highly diverged to the extent that Form B is phylogenetically closer to the sundaicus complex; thus various authors [ 10 , 12 13 ] have considered Form B as a member of the sundaicus complex. Therefore, it is important to identify the correct biological species for the effective management of vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic studies based on ITS2, 28S-rDNA and mtDNA revealed that Form B is closely related to members of the Sundaicus Complex and is far distantly related to Form A. Surendran et al [ 12 ] and Sindhania et al [ 10 ], therefore recommended classifying species B as molecular form B under the Sundaicus Complex. Moreover, Sivabalakrishnan et al [ 13 ] have described species B as An . sundaicus s .…”
Section: Introductionmentioning
confidence: 99%
“…We herein focus on phenomenological growth models (PGMs) that only require a small number of parameters are commonly used to describe epidemic growth patterns, and which can be expressed by an ordinary differential equation (ODE) of the type where is time, is the total size of the epidemic (the cumulative number of cases) at time , is the initial number of cases, is an incidence function that is specific to each PGM under study, and is a vector of parameters. Such models have been used to study the epidemics of influenza [16] , [17] , [18] , Ebola [19] , [20] , [21] , [22] , Zika [23] , [24] , [25] , Chikungunya [26] , and others of global interest. The current COVID-19 pandemic is a scenario for which such models are of obvious importance [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] .…”
Section: Introductionmentioning
confidence: 99%